2022
DOI: 10.1021/acs.joc.1c03008
|View full text |Cite
|
Sign up to set email alerts
|

[4 + 1 + 1] Tandem Cyclization Reaction Involving Isocyanides: Access to 2-(Trifluoromethyl)quinazolin-4(3H)-imines

Abstract: A palladium-catalyzed three-component reaction of isocyanides, 2,2,2-trifluoro-N-(2-iodophenyl)­acetimidoyl chlorides, and amines for the one-pot synthesis of 2-(trifluoromethyl)­quinazolin-4­(3H)-imines was described. The protocol features a wide substrate scope, high efficiency, and readily available raw materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Very recently, Ji, Xu and co-workers developed a palladium-catalyzed [4+1+1] tandem cyclization reaction of trifuoroacetimidoyl chlorides, isocyanides and amines for the one-pot synthesis of 2-(trifluoromethyl)quinazoline-4(3 H )-imines (Scheme 24). 34 The reaction scope was very broad, as verified that different 2,2,2-trifluoro- N -(2-iodophenyl)acetimidoyl chlorides, isocyanides and amines could be smoothly compatible with the reaction system. Compared with the aforementioned carbonylative work reported by Wu and Chen, 28 isocyanides are usually used as a kind of highly reactive C1 synthons via 1,1-insertion.…”
Section: Synthesis Of Cf3-containing Heterocycles From Trifluoroaceti...mentioning
confidence: 65%
“…Very recently, Ji, Xu and co-workers developed a palladium-catalyzed [4+1+1] tandem cyclization reaction of trifuoroacetimidoyl chlorides, isocyanides and amines for the one-pot synthesis of 2-(trifluoromethyl)quinazoline-4(3 H )-imines (Scheme 24). 34 The reaction scope was very broad, as verified that different 2,2,2-trifluoro- N -(2-iodophenyl)acetimidoyl chlorides, isocyanides and amines could be smoothly compatible with the reaction system. Compared with the aforementioned carbonylative work reported by Wu and Chen, 28 isocyanides are usually used as a kind of highly reactive C1 synthons via 1,1-insertion.…”
Section: Synthesis Of Cf3-containing Heterocycles From Trifluoroaceti...mentioning
confidence: 65%
“…In 2022, Ji and co-worker 68 In 2021, Cheng's group 70 synthesized a variety of trifluoromethylimidoyl sulfoxonium ylides (TFISYs) for the first time, and found that these trifluoromethyl building blocks could be used for the preparation of various trifluoromethyl heterocyclics. For example, a lithium-bromide-promoted approach for the preparation of 1,2,3-trisubstituted 5-trifluoromethyl- In 2022, Cheng's group 72 introduced the ruthenium(II)-catalyzed C-H alkylation/amidation of benzoic acids with CF 3imidoyl sulfoxonium ylides, providing an efficient entry to a range of 3-CF 3 isoquinolinones under air conditions (Scheme 55).…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%